2015
DOI: 10.17265/1548-6583/2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Crude Oil Price Forecasting With Statistical Learning Methods

Abstract: Reliable forecasts of the price of oil are of interest for a wide range of applications. For example, central banks and private sector forecasters view the price of oil as one of the key variables in generating macroeconomic projections and in assessing macroeconomic risks. Of particular interest is the question of the extent to which the price of oil is helpful in predicting recessions. This paper presents a statistical learning method (SLM) based on combined fuzzy system (FS), artificial neural network (ANN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Yu et al (2008) made a forecast on crude oil prices with an EMD-based neural network [19]. Slim (2015) improved the forecasting of crude oil prices with statistical learning methods (SLM) based on a combined fuzzy system (FS), artificial neural network (ANN), and support vector regression (SVR) [20]. He et al (2016) showed a significant performance improvement in forecasting WTI and Brent Crude oil prices using a multivariate EMD-based model [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yu et al (2008) made a forecast on crude oil prices with an EMD-based neural network [19]. Slim (2015) improved the forecasting of crude oil prices with statistical learning methods (SLM) based on a combined fuzzy system (FS), artificial neural network (ANN), and support vector regression (SVR) [20]. He et al (2016) showed a significant performance improvement in forecasting WTI and Brent Crude oil prices using a multivariate EMD-based model [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some nonlinear and emerging machine learning models, such as Support Vector Machines (SVMs), Random Forest (RF), Artificial Neural Networks (ANNs), and Genetic Programming (GP), offer effective solutions to nonlinear crude oil price prediction because they overcome the shortcomings of conventional statistical and econometric models [11]. To model and forecast the price of crude oil, for instance, Slim [12] proposed a new Statistical Learning Technique (SLM) based on a combined Fuzzy System (FS), Support Vector Regression (SVR), and ANN. Similarly, several studies revealed that models based on machine learning frequently had some advantages over statistical-based models [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%